Pengaruh Good Governance Terhadap Kinerja Keuangan Perusahaan Perbankan Syariah Yang Terdaftar Di BEI Periode 2022-2023 (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
The purpose of this study is to determine the effect of the implementation of good corporate governance principles through factors such as independent committees, audit committees, good governance, and sharia supervisory boards on the financial performance of Islamic banks. Using data of Islamic banks listed on the Indonesia Stock Exchange in 2022 to 2023, this study found that there is a significant difference between the independent board, audit committee, good governance, and sharia supervisory board in terms of financial return on assets showing that there is no significant effect on the measurement.